Pengaruh Pendidikan Kesehatan dan Pendampingan Bidan terhadap Kepatuhan Ibu Hamil dalam Mengkonsumsi Tablet Besi di Puskesmas Turen - Dian Mayasari; Ratih Mega Septiasari; Tri Astuti Ningsih (Midwifery Department of Sultan Agung Islamic University of Semarang, 2023)
Anemia is a condition in which the number of red blood cells or the concentration of hemoglobin in them is lower than normal or does not meet the body's needs. Danger of anemia for late or undeveloped fetuses, premature birth, low birth weight, risk of damage to vital organs such as brain and heart, in very severe cases. This study aims to determine the effect of health education and midwife assistance on pregnant women's compliance in consuming iron tablets at the Turen Health Center. The research design was pre-experimental with a one group pre-post test design. A sample of 30 respondents who met the inclusion criteria were selected using the accidental sampling technique. The research instruments used were Health Education SAP and SOP for Midwife Assistance and compliance checklist sheets. Data analysis used the Wilcoxon Sign Rank Test non-parametric statistical test. The results showed p = 0.00 (p <0.05), so it could be interpreted that there was an influence of health education and midwifery assistance on pregnant women's compliance in consuming iron tablets at the Turen Health Center. The implementation of health education and midwife assistance can have an impact on pregnant women's compliance. Midwives are expected to implement health education and provide optimal assistance so that pregnant women regularly consume iron tablets so that they can prepare themselves for the birth process and can reduce complications during pregnancy.